HYDROMETRA IN A NON DESCRIPT QUEEN CAT - S. Sathishkumar; S. Rangasamy (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A two year-old queen cat with unknown mating history revealed absence of clear indication of positive pregnancy but single fluid filled anechoic structure noticed on ultrasonography. Spaying was performed and clear watery sterile fluid in the uterus confirmed it as a case of hydrometra.